Insecure Attachment Styles and Phubbing: The Mediating Role of Problematic Smartphone Use - Juhyung Sun; Claude H. Miller (Human Behavior and Emerging Technologies)
Lately, increasing concern has focused on the incessant and intrusive use of smartphones across a wide range of interpersonal and relational contexts. Of concern is that many people appear to snub someone during face-to-face interactions by focusing more on their smartphone than on their relational partner, namely, phubbing. Individuals with insecure attachment styles may phub their intimate others more often. However, such relationships have not been examined. This study used a cross-sectional design to examine key relationships between insecure attachment styles on phubbing. An online survey was conducted to examine the relationships between the variables of this study (N=444, 72% female: mean age 20). The analyses revealed both anxious-preoccupied and dismissive-avoidant attachment styles to be positively associated with phubbing. Moreover, both insecure attachment styles indirectly predicted phubbing through problematic smartphone use (PSU). Insecure attachment styles appear to impact how often people phub others within intimate relationships, and further, PSU may function as a mechanism linking these insecure attachment styles with phubbing.